(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the life, scientific activity, and spiritual legacy of Academic Haji-Akbar Rahmangulov, who made a significant contribution to the development of civil law, business law, and international private law in the Republic of Uzbekistan. It also provides an in-depth analysis of his scientific research, his dedication to mentoring students, and his role in legal education and legislative reforms.